Capturing country images: a methodological approach. Issue 2 (3rd July 2021) - Sevin, Efe; Ayhan, Kadir Jun; Ingenhoff, Diana
ABSTRACT: Country images have been notoriously difficult to capture and measure effectively. In this article, we propose a methodological approach that combines designed and found data to capture public attitudes. We demonstrate how a mixed-method design with survey data and digital data – namely tweets and Google Trends – make it possible to better capture what target audiences think about a country. We make the case for such a combination by highlighting three aspects of country images. First, to understand what different types of public think about a country, we need to listen to different voices, and complement standardised public opinion survey data with open questions and digital data. Second, social media platforms are invaluable data resources as well as outlets that people on social media turn to for news and information. Last, digital data is unique and powerful, but difficult to analyse and interpret to create value for developing strategic communication policies. Public opinion survey data can help structure digital data and link both outcomes with each other. We support our methodological arguments through an illustrative study of the South Korean country image. We conclude our article by presenting a roadmap for multi-method analysis.